2021
DOI: 10.1002/cphc.202000831
|View full text |Cite
|
Sign up to set email alerts
|

The Cytotoxic Effect of α‐Synuclein Aggregates

Abstract: Parkinson's disease is a neurodegenerative disorder involving a functional protein, α‐synuclein, whose primary function is related to vesicle trafficking. However, α‐synuclein is prone to form aggregates, and these inclusions, known as Lewy bodies, are the hallmark of Parkinson's disease. α‐synuclein can alter its conformation and acquire aggregating capacity, forming aggregates containing β‐sheets. This protein's pathogenic importance is based on its ability to form oligomers that impair synaptic transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Aggregation of proteins into toxic species is a hallmark of many diseases known as proteinopathies, including the amyloid-β (Aβ) peptides and tau proteins in AD [43], the α-synuclein (α-Syn) protein in Parkinson's disease [44,45], the prion (PrP) protein in Creutzfeldt-Jakob disease [46,47] and the huntingtin protein in Huntington's disease [48]. In vivo, the protein aggregates can be detected after staining with a dye or other biomarker.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation of proteins into toxic species is a hallmark of many diseases known as proteinopathies, including the amyloid-β (Aβ) peptides and tau proteins in AD [43], the α-synuclein (α-Syn) protein in Parkinson's disease [44,45], the prion (PrP) protein in Creutzfeldt-Jakob disease [46,47] and the huntingtin protein in Huntington's disease [48]. In vivo, the protein aggregates can be detected after staining with a dye or other biomarker.…”
Section: Introductionmentioning
confidence: 99%
“…A common structural motif in the fibrillar aggregates is the "cross-β structure", which consists of repeated units of β-strands positioned perpendicular to the fibril axis, stabilised by inter-strand hydrogen bonds aligned along the direction of the fibril axis [54,55]. The main toxic species in many proteinopathies appears not to be the large protein aggregates but rather small soluble intermediate oligomers that form along the aggregation pathways [44,46,48,56]. Being important potential drug targets, these oligomers have been extensively researched, but their sizes, shapes and structures remain unclear [49].…”
Section: Introductionmentioning
confidence: 99%
“…Once we labeled the cells incubated with aggregates formed by tau and α‐syn peptide, the staining also appeared as dots and blobs suggesting the presence of aggregates in the periphery (Figure 5 B–C). Previously, we demonstrated that α‐syn aggregates can promote cell death by diminishing the cohesion of the membrane of cells, [34] , thus we decided to test the cells against these types of aggregates by staining the samples with DAPI and using the phase to check the cells and nuclei morphologies, respectively. In control cells, (Figure 6A) the morphology showed cells with neurite‐like structures after retinoic acid induction and a regular chromatin distribution in the nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid membrane fluidity is essential for the efficient binding of alpha-synuclein [156]. If aberrant lipid homeostasis occurs, this may alter the lipid membrane composition or fluidity and the binding of alpha-synuclein, leading to subsequent neurotoxicity [114,157,158]. Alterations in the lipid composition have been reported in PD brains, including changes in levels of fatty acids and the lipid raft content [159].…”
Section: Lipid Homeostasismentioning
confidence: 99%